Identification of Mineralocorticoid Receptors, Aldosterone, and Its Processing Enzyme CYP11B2 on Parasympathetic and Sympathetic Neurons in Rat Intracardiac Ganglia - Dehe, Lukas; Mousa, Shaaban A.; Aboryag, Noureddin; Shaqura, Mohammed; Beyer, Antje; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Neuroanatomy, 2022)
Recent interest has focused on the mineralocorticoid receptor (MR) and its impact on the myocardium and the performance of the heart. However, there is a lack of evidence about MR expression and its endogenous ligand aldosterone synthesis with specific regard to the intrinsic cardiac nervous system. Therefore, we looked for evidence of MR and aldosterone in sympathetic and parasympathetic neurons of intracardiac ganglia. Tissue samples from rat heart atria were subjected to conventional reverse-transcriptase polymerase chain reaction (PCR), Western blot, and double immunofluorescence confocal analysis of MR, corticosterone-inactivating enzyme 11β-hydroxysteroid-dehydrogenase-2 (11β-HSD2), aldosterone, and its processing enzyme CYP11B2 together with the neuronal markers vesicular acetylcholine transporter (VAChT) and tyrosine hydroxylase (TH). Our results demonstrated MR, 11β-HSD2, and CYP11B2 specific mRNA and protein bands in rat heart atria. Double immunofluorescence labeling revealed coexpression of MR immunoreactivity with VAChT in large diameter parasympathetic principal neurons. In addition, MR immunoreactivity was identified in TH-immunoreactive small intensely fluorescent (SIF) cells and in nearby VAChT- and TH-immunoreactive nerve terminals. Interestingly, the aldosterone and its synthesizing enzyme CYP11B2 and 11β-HSD2 colocalized in MR– immunoreactive neurons of intracardiac ganglia. Overall, this study provides first evidence for the existence of not only local expression of MR, but also of 11β-HSD2 and aldosterone with its processing enzyme CYP11B2 in the neurons of the cardiac autonomic nervous system, suggesting a possible modulatory role of the mineralocorticoid system on the endogenous neuronal activity on heart performance.